Effect of complex and contrast resistance and plyometric training on selected strength and power parameters - Suthakar Krishnaswamy1, Annida Balakrishnan2, G. Rajamohan1*, P. Kanagasabai1, (Journal of Experimental Sciences, 2011)
The purpose of this study was to evaluate the effects of a complex training program, a combined practice of weight training and plyometrics, and contrast resistance and plyometric training on selected strength and power parameters in young healthy athletes. Thirty young male athletes, aged 19â€“21 years old, from the Department Of Physical Education and Sports Sciences, Annamalai University were selected as subjects. They were grouped into two with fifteen members of each. Group 1 served with complex training programÂ  and Group 2 with contrast training program. Experimental training was given for 3 months duration (4 days/week). Selected strength such as leg strength, back strength, muscular strength, strength endurance and power parameters includes explosive power in terms of vertical and horizontal distances were assessed using appropriate test items. Data were collected before and after training period and statistical analysis was done using paired T- test significantly effective at 0.05 level of confidence. Hence our results support the use of contrast training to improve the upper and lower body explosivity levels in young players. In conclusion, this study showed that more strength conditioning is needed during the sport practice season. Furthermore, we also conclude that contrast training is a useful working tool for coaches, innovative in this strength-training domain, equally contributing to a better time-efficient training.